History of the World Allergy Organization: Time to Change! - S.G.O. Johansson, MD, PhD (World Allergy Organization Journal, 2011)
History of the World Allergy Organization: In 1951, the leaders in allergy from all over the world came together to form the International Association of Allergology and Clinical Immunology (IAACI). For the next 60 years, the allergy world converged at the IAACI triennial meetings, which became biennial in 2003. The international meetings, originally named the International Congress of Allergology and Clinical Immunology (ICACI), are now the World Allergy Congress (WAC) hosted by the World Allergy Organization (WAO). Everyone who has aspired to have worldwide recognition has played a part in IAACI-WAO. The History of the World Allergy Organization traces the global arc of the allergy field over the past 60 years. The current officers of WAO elected to focus on this rich history, inviting prominent leaders who are interested in being part of this history project to write about their time with IAACI-WAO. This series will be presented in Cancún, México, as part of the XXII World Allergy Congress (December 4-8, 2011). Leading up to the Congress in Cancún, the World Allergy Organization Journal is presenting segments of the History as part of the ''Notes of Allergy Watchers Series.'' Please enjoy.--Michael A. Kaliner, MDHistorian and Past President (2006-2007)World Allergy Organization